Studies of VOPcPhO and PTCDA thin films and their application in organic solar cells / Lim Lih Wei - Lim, Lih Wei (2012)
This work is focused on the study of the p-type organic semiconductor, vanadyl 2, 9, 16, 23-tetraphenoxy-29H, 31H-phthalocyanine (VOPcPhO) and n-type organic semiconductor of 3, 4, 9, 10-perylenetetracarboxylic dianhydride (PTCDA) as the possible candidates for organic photovoltaic cells (OPVC) fabrication. The initial phase of this work involved preparation and characterisation of organic semiconductor thin films. The VOPcPhO thin films were prepared by spin-coating method while the PTCDA thin films were deposited by thermal evaporation technique using a homebuilt thermal evaporator in Low Dimensional Materials Research Centre (LDMRC). The optical and structural properties of the deposited thin films were characterised by ultraviolet-visible (UV-VIS) spectroscopy, x-ray diffraction (XRD) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM). The UV-VIS absorption spectra revealed that the absorption bands of VOPcPhO and PTCDA thin films are in complimentary to each other. PTCDA absorbs most light in the visible range between 450nm to 600nm, whereas VOPcPhO absorbs light in the UV range between 300nm to 400nm as well in the near infrared region of 600nm to 800nm. Therefore, by combining these two organic semiconductors of PTCDA and VOPcPhO to form a bilayer heterojunction, hence a good coverage of the solar spectrum can be explored. The estimated optical band gap, Eg determined for the single layer VOPcPhO and PTCDA thin films as well as bilayer VOPcPhO/PTCDA thin film are 1.6eV, 2.13eV and 1.62eV, respectively. Low optical band gap is favourable in OPVC because relatively low photon energy is required to excite the electron in the material to form exciton (bound electron-hole pair). The second phase of this work involves the fabrication of OPVC using VOPcPhO and PTCDA thin films. Single layer and bilayer heterojunction structure OPVC were constructed and the performance of these devices were determined and compared by J-V curve. It was found that the single layer devices did not exhibit photovoltaic effect but the bilayer heterojunction devices clearly shown interesting photovoltaic effect when light beam shined upon them. This finding has indicated that the exciton dissociations can only take place at the VOPcPhO/PTCDA interface. However, the power conversion efficiency (PCE) of the primitive OPVC was very low (0.16×10-3%). The final phase of this work involved the improvements and optimisations of the OPVC. Insertion of hole transport layer, oxygen plasma treatment, thickness optimization, post thermal annealing and vapour treatments were performed in attempts to raise the PCE of the OPVC. Insertion of poly(3,4-ethylenedioxythiophene: poly(styrenesulfonic acid) (PEDOT: PSS) and oxygen plasma treatment are promising methods to improve the OPVC. However, post thermal annealing and vapour treatments were unsuccessful to improve the OPVC. The highest PCE determined for the bilayer heterojunction OPVC after went through the treatments is 3.71×10-3%. Attempts of multilayer heterojunctions OPVC was made in order to further prove the exciton dissociations can only take place at the VOPcPhO/PTCDA interfaces. The multilayer heterojunctions OPVC has a PCE of 5.40×10-3%.